Subjects with osteoporosis to remain at high risk for fracture despite benefit of prior bisphosphonate treatment—a Danish case-control study. Issue 1 (January 2017) - Hansen, L.; Petersen, K.; Eriksen, S.; Gerstoft, F.; Vestergaard, P.
Abstract Summary The benefits of pharmaceutical treatment for osteoporosis may be limited for a number of patients, as they continue to experience fractures. Alternative treatments may be considered for subjects whom remain at high risk for future fractures. Introduction Previous studies have investigated the effects of good adherence to anti-osteoporosis medication. However, very few studies have described why some patients experience fractures and loss of BMD despite adherence to treatment. The aim of this study was to estimate the proportion of patients at high risk for fracture despite being compliant to bisphosphonate treatment and examine which factors influence why some osteoporotic patients remain at a high risk for fracture despite being compliant to bisphosphonate treatment. Methods This case-control study is based on Danish national health registry data. The subjects had to have either one BMD test or a fracture prior to inclusion. "High-risk" subjects (cases) were defined as BMD t-score < =−2.5 SD, any drop in BMD from baseline or a fracture 24–36 months following inclusion. Results A total of 2406 subjects (66.3 % women; 33.7 % men) fulfilled the inclusion criteria, and of these, 352 (14.6 %) were identified as high risk subjects. A multiple logistical regression analysis showed that high risk subjects were more likely to have lower plasma calcium and/or vitamin D levels (OR: 2.9) and were more frequently diagnosed with hyperparathyroidism (OR: 2.6). Conclusion Based on Danish national health registry data, 14.6 % patients were identified as patients remaining at high risk for fracture despite being compliant to bisphosphonate treatment. Lower plasma calcium and/or vitamin D level is the greatest predictor of high risk for fracture despite persistent bisphosphonate treatment. Secondary causes of osteoporosis should be considered and alternative treatments may be advised for subjects whom remain at high risk.